Integrasi Kearifan Lokal dalam Pembelajaran IPS untuk Menumbuhkan Nilai Karakter Pada Siswa Sekolah Dasar - Rismawati, Lia; Al-Pansori, Muh. Jaelani; Ayu Pransisca, Made (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to describe the integration of local wisdom into Social Studies (IPS) learning as an effort to develop character values in elementary school students. A qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The results show that IPS learning based on local values such as mutual cooperation, tolerance, responsibility, and respect for culture significantly enhances students’ active engagement. Learning activities that connect academic material with students’ social realities foster more meaningful understanding and strengthen character values contextually. This integration not only revitalizes local culture within the classroom but also deepens students' connection with their social identity and environment. The main challenges in implementation include limited local teaching resources, lack of teacher training, and insufficient support from schools and parents. The study concludes that local wisdom-based IPS learning has strong potential to shape students' character, though systematic support and educational policies are needed to ensure sustainable implementation.